Humoral immune responses of experimentally Eimeria ninakholyakimovae-infected goat kids. (April 2017) - Matos, Lorena; Muñoz, María del Carmen; Molina, José Manuel; Ferrer, Otilia; Rodríguez, Francisco; Pérez, Davinia; López, Adassa María; Martín, Sergio; Hermosilla, Carlos; Taubert, Anja; Ruiz, Antonio
Highlights: Eimeria ninakohlyakimovae induces increased levels of seric IgG and IgM in goats. Eimeria ninakohlyakimovae induces increased levels IgA in ileal mucus of goats. Goat IgGs immuno-react with sporulated oocyst antigen of Eimeria ninakohlyakimovae . Levels of IgG, IgM and IgA do not correlate with Eimeria ninakohlyakimovae OPG counts. Abstract: Although cellular immune reactions seem to be crucial for protective immune responses in Eimeria spp. infections, there are also evidences on an active involvement of the humoral counterpart. In the present study, we have analyzed the humoral response of goat kids subjected to primary and challenge infections with Eimeria ninakholyakimovae . Specific levels of IgG and IgM in serum samples and IgA in the ileal mucus were estimated. In infected kids, significantly increased levels of IgG were observed from 3 weeks post infection onwards in addition to an enhancement of specific IgM and secretory IgA levels. A wide range of peptides of sporulated oocyst antigen (SOA) was recognized by specific IgG as determined by immunoblotting. However, no correlations were found between immunoglobulin levels and OPG counts after challenge infection. Overall, these data indicate a significant specific humoral response of E. ninakohlyakimovae -infected goat kids that does not seem to convey immunoprotection. Further studies should be addressed to clarify if the lack of correlation might be associated to the type of antigen used for the immunoenzimatic assays, the age of the animals or other factors.